2019
DOI: 10.1039/c9py00226j
|View full text |Cite
|
Sign up to set email alerts
|

A continuing legend: the Brookhart-type α-diimine nickel and palladium catalysts

Abstract: Here we will summarize some of the recent advances in α-diimine ligand developments, as well as some new and challenging monomers that this class of catalysts can address through these ligand improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
194
2
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 268 publications
(206 citation statements)
references
References 165 publications
(217 reference statements)
7
194
2
3
Order By: Relevance
“…Complex Ni2 bearing strong electron‐withdrawing fluorine substituent of para ‐position in anilinic moiety demonstrated higher activity and higher molecular weights than the corresponding Ni2 (Table , entries 1–3 vs 4−6), probably because of the increased electrophilicity. This differences seen are consistent with previous literature on Brookhart‐type catalyst studies . We suggest that an interaction between the fluorine atoms and Al (III) activators blocks the apical positions of the catalytically active nickel center, which may reduce effectively associative olefin exchange reactions .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Complex Ni2 bearing strong electron‐withdrawing fluorine substituent of para ‐position in anilinic moiety demonstrated higher activity and higher molecular weights than the corresponding Ni2 (Table , entries 1–3 vs 4−6), probably because of the increased electrophilicity. This differences seen are consistent with previous literature on Brookhart‐type catalyst studies . We suggest that an interaction between the fluorine atoms and Al (III) activators blocks the apical positions of the catalytically active nickel center, which may reduce effectively associative olefin exchange reactions .…”
Section: Resultssupporting
confidence: 91%
“…The branching structures analysis based on 13 C NMR showed that only 28 methyl branches were observed for Ni2 at 25 °C (Figure , Table , entry 4). The lower degree of branching density for the sterically bulkier catalysts are probably due to the relatively greater preference of insertion of ethylene into a primary metal alkyl species versus insertion into a secondary metal alkyl species …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition‐metal‐catalyzed olefin copolymerization with polar comonomers represents an efficient and attractive route for introducing functional groups that can improve polyolefin properties . Recently, several palladium‐ and nickel‐based catalysts have been reported with these capabilities . For example, phosphine sulfonate and related palladium catalysts have been extensively studied and can copolymerize ethylene with various polar comonomers …”
Section: Introductionmentioning
confidence: 99%
“…Nickel and palladium based complexes supported by different types of ligands have been extensively utilized as olefin oligo/polymerization catalysts for decades both in academia and industry because of their low oxophilicity and copolymerizing capability of the olefin with polar comonomers . The chain‐walking process has received extensive researches in ethylene oligo−/polymerization using these catalysts to produce polyethylene (PE) possessing unique branched structures .…”
Section: Introductionmentioning
confidence: 99%